The genesis of American aesthetics: Pioneers, colonial spirit and the resignification of the aesthetic experience in the 19th century - Haubert, Laura Elizia; Fabio; Viale, Claudio Marcelo (Metafísica y Persona, 2022)
In this article we propose a general approach to the emergence of aesthetics in 19th century American culture. Using a historical-critical approach, we develop this work in three parts. First, we analyze the features of the two dominant interpretive theories, whose core argument consists in sustaining the absence of an American aesthetic tradition in the 19th century. The theory of the "pioneer influence", on the one hand, is associated with the thesis that the absence of an American aesthetics in the 19th century is due to a materialistic culture and refractory to art generated from the figure of the pioneer. The "cultural colonization" theory, on the other hand, revolves around the idea of a passive importation of cultural paradigms from Europe as a characteristic feature of American aesthetics of the time. Second, we argue that in the works of many American thinkers since (at least) the nineteenth century there are sketches that lay the foundation for American aesthetic culture. The relevance of the works of these authors, frequently unjustly forgotten, is overlooked due to the limitations of the dominant theories mentioned (the theory of "pioneer influence" and that of “cultural colonization "). Finally, starting from what developed in the previous point, we argue that it is possible to develop an alternative interpretation to the two dominant theories, which highlights the fragmentary, discontinuous and interdisciplinary nature of the emergence of aesthetics in the 19th century United States. This interpretation (in this article only outlined) is fundamental, in our opinion, to have a complete understanding of the systematic emergence of American aesthetics (whether we place it in the work of George Santayana or in that of John Dewey) and the various ways in which they thematized about aesthetic experience in its context.